Protocol for isolating small cytosolic dsDNA from cultured murine cells - Zhizheng Dai; Hongyu Ji; Anqi Zheng; Ai-Long Huang; Kai-Fu Tang (STAR Protocols, 2024)
Summary: We recently identified a class of small cytosolic double-stranded DNA (scDNA) approximately 20–40 bp in size in human and mouse cells. Here, we present a protocol for scDNA isolation from cultured murine cells. We describe steps for cytosolic compartment separation, DNA isolation in the cytosolic fraction using phenol-chloroform extraction, and ethanol precipitation. We then detail procedures for denaturing purified cytosolic DNA through urea polyacrylamide gel electrophoresis and obtaining scDNA in the cytosolic DNA fraction via gel purification.For complete details on the use and execution of this protocol, please refer to Liu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.